(untitled) (Research, Society and Development, 2020)
In Brazil, the right to health has constitutional universal provision. However, its incompleteness and the scarcity of structural and human resources leads people who would benefit from access to specific health services, mainly the ones in intensive care need - as currently intensified by the COVID-19 pandemic -, to appeal to judicial way to obtain access to them. The aim of this study was to problematize the relation between the insufficient number of ICU (Intensive Care Unit) beds at the current demands for them due to the COVID-19 pandemic through judicialization. The data from the Ministry of Health database were confronted with the literature on the judicialization of health within the national scope, with attention to the statistical data of Pará state’s Court of Justice. There were 14 actions aimed at guaranteeing access to the ICU beds in the period from 03/20/2020 to 05/25/2020 in Pará state. The availability of these in the state (1,718) represents 9% of the total number of beds, below the national average, both beneath the ideal determined by the World Health Organization (ideal rate of 3 to 5 ICU beds for every thousand inhabitants). In conclusion, the judicialization of health can be a sign of dysfunctions and failures in the management of the health systems, evidenced by the COVID-19 pandemic, which could lead to the possibility of scarcity of health resources in the country.